Foreign language learning and teaching style preferences in Malaysian universities / Neo Swee Leng - Neo, Swee Leng (2013)
his study focuses on foreign language learning in Malaysian universities. It specifically examines the learning style preferences of Malaysian tertiary-level learners of Spanish as a foreign language (SFL), teaching style preferences of Spanish language teachers and the match between and among them. Furthermore, it explores the relationship between a match of learning and teaching style preferences and learners’language achievement.The study is a mixed methods design and data was collected using Perceptual Learning Style Preference Questionnaire (PLSPQ), Teaching Style Questionnaire(TSQ), interviews and class observations. The subjects consisted of 232 SFL learners and nine teachers from four public universities in Malaysia.The findings showed that the learners preferred multiple learning styles. They strongly preferred kinesthetic, auditory and tactile learning styles. However, they were also keen about the group, visual and individual learning styles. On the other hand,gender is not significantly related to language learning styles but ethnicity to some extent does. Moreover, this study revealed that the teachers had a variety of teaching style preferences, with major preferences for auditory, visual and group teaching styles. However, they did not mind using kinesthetic, tactile and individual teaching styles.Both male and female teachers had four major teaching styles respectively. The Filipino teachers had five preferred teaching styles, the Malaysian teachers and Mexican teacher strongly preferred three teaching styles while the Spanish teachers strongly preferred only two teaching styles. In this study, it is apparent that teachers who had a higher number of years of teaching Spanish in Malaysia appeared to have more major preferred teaching styles than those who had less teaching experience in Malaysia. The longer the teachers had taught the language, the more major teaching style preferences they had.This study also revealed that learning and teaching style preferences of students and teachers did not match. The mismatch occurred in visual, kinesthetic, tactile and group styles. It was also discovered that a match of learning and teaching style preferences did not correspond with the Spanish achievement of Teacher 1’s (T1), T2’s,T3’s, T4’s, T5’s and T7’s students. However, it did correlate statistically and negatively with the achievement of T6’s students. This signified that students did not get good language achievement even though their preferred learning styles matched the teacher’s teaching styles. Conversely, they still achieve good examination grades even though there was a mismatch between their learning style and their teachers’ teaching style preferences. As a conclusion, the mismatch of teaching and learning style preferences did not affect the learners’ language achievement between the individual teacher and his/her students within the group. However, it affected the students’emotional well-being, that is, they were frustrated, bored and anxious.These findings will be useful to both learners and teachers in both maximizing and enhancing the former’s learning potential, as well as making the latter more efficient and effective in their teachings.